Integrando a sustentabilidade na formação de administradores - Telles, Beatriz Marcos (2011)
The issue of sustainability is beginning to be integrated into institutions of higher education. Decision-making in the corporate environment requires that consider the social and environmental dimensions, as well as economic, especially with the current crisis of civilization in which we live. New knowledge, learning and attitudes are required in the training of administrators, leaders and managers, for a new consciousness may arise with new attitudes towards the Consumer Society, the exploitation of the planet's natural resources, competition, cooperation, power and ethics. Education for sustainability is necessary at this time in the 21st century, based on complex thinking, interdisciplinarity, on ecological literacy and collaborative learning, requiring for such new knowledge and changing attitudes of those involved. This report explores issues related to the topic of sustainability and education, particularly in relation to the training of administrators, as well as the challenges faced in the implementation of new proposals. Displays a list of creative and innovative educational practices to enrich the approach and suggests ways for this new time and its challenges. Does presentation of the Administration in Brazil and in PUC-SP, and presents the ongoing process of implementing the discipline of Sustainability in Bachelor of Management at PUC-SP, analyzing and discussing in particular the results of a research with teachers of this subject, as well as shows other ways that other institutions of higher education are crossing through this purpose. The report speaks with the national and international literature, in order to encourage educators and managers for the collective construction of an education for sustainability, where all stakeholders of the educational process can become more conscious, responsible and committed to life on the plane